Psychological Impact of Presymptomatic X-Linked ALD Diagnosis and Surveillance: A Small Qualitative Study of Patient and Parent Experiences - Cecilie S. Videbæk; Sabine W. Grønborg; Allan M. Lund; Mette L. Olesen (International Journal of Neonatal Screening)
X-linked adrenoleukodystrophy (ALD) is a rare metabolic disorder. Symptoms range from cerebral demyelination (cALD) to adrenal insufficiency and slowly progressive myeloneuropathy. cALD is fatal if not treated with hematopoietic cell transplantation in the early stages of the disease course. This can be achieved through cascade testing or newborn screening (NBS). Due to the lack of predictive measures of disease trajectory, patients are monitored with frequent MRI scans and hormone testing to ensure timely intervention. With this study, we wanted to explore how the diagnosis of ALD, before the development of cALD, and the follow-up program affected patients and their parents. Using semi-structured interviews, we interviewed seven parents of children with ALD aged 3–11 and four patients with ALD aged 18–25. Because NBS for ALD has not been implemented in Denmark, the patients were identified through either cascade testing or after having presented with adrenal insufficiency. We generated five themes: (I) ALD patients maintained mental resilience despite diagnosis and surveillance; (II) patients’ concerns matured with age and centered around situations that confronted them with their patient status; (III) parents of children with ALD had both short-term and long-term worries for their children’s health; (IV) parents took on a huge psychological burden; and (V) due to its rarity, the diagnosis of ALD evoked a sense of isolation and disease-related loneliness. Overall, we found a large discrepancy in the experiences reported by parents and patients. Despite the small sample size, we identified patterns that suggest that while the early diagnosis took a significant psychological toll on the parents, patients lived relatively carefree lives despite their ALD diagnosis.